2021
DOI: 10.18415/ijmmu.v8i12.3176
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sustainable Food Agricultural Land (LP2B) Using Spatial Approach South Pringsewu District

Abstract: This study aims to examine the distribution pattern and factors that influence the distribution of Sustainable Food Agricultural Land (LP2B) in the southern part of Pringsewu Regency in 2020. This study uses a descriptive research method. The population in this study were 9 sub-districts in Pringsewu district and the research samples were Pringsewu District, Gading Rejo District, Ambarawa District, Pardasuka District, and Pagelaran District. In this study data collection using observation, interviews and docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sustainable agricultural land emphasizes substantial food sovereignty [71,72]. The availability of data on spatial form as well as from survey results is an important prerequisite for realizing protection efforts according to the mandate of Law Number 41 of 2009.…”
Section: Environmental Carrying Capacity Model For Sustainable Food A...mentioning
confidence: 99%
“…Sustainable agricultural land emphasizes substantial food sovereignty [71,72]. The availability of data on spatial form as well as from survey results is an important prerequisite for realizing protection efforts according to the mandate of Law Number 41 of 2009.…”
Section: Environmental Carrying Capacity Model For Sustainable Food A...mentioning
confidence: 99%
“…(2020) [9] The study focuses on the implementation and efficacy of the Sustainable Food Agriculture Land Protection (PLP2B) policy in addressing agricultural land conversion challenges in the light of climate change. Miswar et al (2021) [13] The research is being carried out in the southern part of Pringsewu Regency with the goal of investigating the distribution pattern of Sustainable Food Agricultural Land (LP2B) and determining the elements that influence it. Rohmah et al…”
Section: Lanya Et Al (2016) [23]mentioning
confidence: 99%
“…In the context of agricultural land protection, the Government has issued Law No. 41/2009 on the Protection of Sustainable Food Agricultural Land (PSFAL) to control land conversion and protect farmers' rights [9,10].Several studies have examined the implementation of this policy in several locations, such as Sukabumi [10], Tasikmalaya [11], Tegal [12], Pringsewu [13], Sukoharjo [14], Banyuwangi [15], Banten [16], Kulonprogo [17], Pati [18], Indragiri Hilir [19], East Kalimantan [20], Gowa [21], and so on. The results of the study found that the implementation of the regulations experienced several obstacles, including weaknesses in law enforcement by the government and potential conflicts of interest between the local and central governments.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial plan map with the possibility of being expanded for sugarcane plantations consists of cultivation areas in the form of plantations, dry fields/fields, and rainfed rice fields. Food agricultural land in the form of protected agriculture was excluded from the analysis to ensure that it does not interfere with the fulfillment of staple food needs [55][56][57]. The location on the forest area map that can be used to expand sugarcane plantations was included in the area of other uses, namely undesignated regions.…”
Section: Land Availability Analysismentioning
confidence: 99%